Evaluation of knowledge and experience of dentists of São Paulo State, Brazil about cardiopulmonary resuscitation - Gonzaga, Heron Fernando de Sousa; Buso, Leonardo [UNESP]; Jorge, Maria Augusta; Gonzaga, Lúcia Helena de Sousa; Chaves, Marcelo Donizetti; Almeida, Oslei Paes de (Fundação Odontológica de Ribeirão Preto, 2003)
Este trabalho descreve o conhecimento e experiência dos cirurgiões dentistas em reanimação cárdio-respiratória (RCR). Foram entrevistados 182 cirurgiões dentistas do Estado de São Paulo, Brasil: 59% julgava-se capaz de definir RCR, embora somente 46% tivesse um conceito correto; 54% acreditava ser capaz de realizar RCR, no entanto nenhum deles referiu ter recebido treinamento prático em RCR; 3% dos entrevistados mencionou a ocorrência de parada cárdio-respiratória no consultório odontológico. Concluiu-se que os cirurgiões dentistas brasileiros deveriam ser melhor treinados em emergências médicas que podem ocorrer nos consultórios odontológicos.

This work describes the knowledge and experience of dentists about cardiopulmonary resuscitation (CPR). A total of 182 dentists from São Paulo State, Brazil were interviewed: 59% judged themselves able to define CPR, although only 46% had a correct concept; 54% believed himself to be able to perform CPR, however, none of them referred to have received practical training in CPR; 3% of the interviewed professionals mentioned the occurrence of cadiopulmonary arrest in their dental office. It was concluded that dental surgeons in Brazil should be better trained for medical emergencies that can occur in the dental office.
Keywords: dentistry; cadiopulmonary arrest; cardiopulmonary resuscitation